FLUORESCENCE IN SITU HYBRIDIZATION TO DETERMINE THE GENOMIC CHANGES IN CHROMOSOME 17 AND P53 GENE IN ORAL LEUKOPLAKIA PATIENT IN INDIAN POPULATION: A CROSS-SECTIONAL STUDY. - Rathore, Kanika; Singh, Mohan; Khatri, Dr. Garima; chodankar, Simran (Student's Journal of Health Research Africa, 2024)
Introduction Oral cancer, especially squamous cell type, is common, with 274,000 instances annually. The risk of oral cancer from leukoplakia, a white patch at least 5 mm in size, has been extensively investigated. Globally, leukoplakia prevalence ranges from 2.6% to 4.1%. It usually develops after 30, peaks over 50, and is associated to tobacco, alcohol, and betel quid use. Leukoplakia-related chromosomal abnormalities can be revealed by Fluorescence in situ hybridization (FISH). Objective The goal of research is to clarify the genetic mechanisms behind the development of leukoplakia by examining p53 gene changes and numerical aberrations in chromosome 17 in Indian populations. Material and methods In this cross-sectional study, FISH was used to diagnose 50 cases of Oral leukoplakia (OLP), utilizing the " Locus Specific Identifier (LSI) TP53/Centromere Enumeration Probe (CEP) 17 FISH Probe Kit " to determine the copy number for CEP 17 (green) at the centromere of chromosome 17 and LSI TP53 (orange) at chromosome 17p13.1. Results Three of the fifty cases in the analysis show molecular change. In roughly 4% of instances, p53 gene amplification and chromosome 17 polysomy were present, while 2% of cases only had p53 gene deletion. In the investigation, grade 3 and grade 4 oral leukoplakia showed all aberrations, and the highest 18 subjects (n=18) out of 50 individuals (36%) had a tobacco and/or smoking addiction. Conclusion The research illuminates molecular abnormalities in “chromosome 17” and the “p53” gene in Indian OLP patients. The study helps bridge research and clinical practice to improve oral leukoplakia genetic diagnosis and management. This will enhance patient outcomes by preventing such events. Recommendations Implement routine screening for genetic alterations in chromosome 17 and the p53 gene in patients with oral leukoplakia to enhance early detection and targeted intervention strategies.